Toward greener geotechnology: Coconut shell columns for clay soil stabilization - Ng, Jun Shen; Muzamir, Hasan; Ieszaliana, Ali; Hoque, Md. Ikramul (Springer Nature, 2026)
Repurposing biomaterials such as coconut shell can be a sustainable and financially feasible approach in modifying the technique of traditional stone columns in ground renovation. This method effectively improves weak clay soils, addressing issues such as particle dispersion and high compressibility. While previous studies have noted the benefits of coconut shell, few have emphasized statistical analysis. The present study demonstrates the capability of kaolin reinforced with ground coconut shell columns. Fundamental soil behaviors were assessed through grain size distribution, Atterberg limits, specific gravity, Proctor compaction, relative density, and permeability, while advanced properties were evaluated using unconfined compression and unconsolidated undrained tests on both unreinforced and reinforced samples. Evaluation of potential factors in manipulating the soil’s strength was implemented in the ratio of reinforcement penetration, reinforcement penetration to diameter, reinforcement volume, and effective confining pressure. The results verified the effectiveness of coconut shell granular columns at varying ratios, aligned with its diameter and height. Correlation equations applied to shear strength data yielded R2 values greater than 0.9 for all designs, except the 16 mm diameter reinforcement. The GCS1080 specimen achieved the maximum shear strength improvement of 24.62 kPa or 73.38% compared to unreinforced specimen. Cohesion and friction angle reached 82 kPa and 32°, with respective increases of 66.33% and 6.67%. Regression analysis established a streamlined function that incorporates all relevant variables, with R2 = 0.9174. Conclusively, the findings validate coconut shell as a granular substitute that strengthens clayey soil, supports sustainable material use, and aligns with the Sustainable Development Goals